Ecogenomics sheds light on diverse lifestyle strategies in freshwater CPR - Chiriac, Maria-Cecilia; Bulzu, Paul-Adrian; Andrei, Adrian-Stefan; Okazaki, Yusuke; Nakano, Shin-Ichi; Haber, Markus; Kavagutti, Vinicius Silva; Layoun, Paul; Ghai, Rohit; Salcher, Michaela M (Microbiome, 2022)
BACKGROUND: The increased use of metagenomics and single-cell genomics led to the discovery of organisms from phyla with no cultivated representatives and proposed new microbial lineages such as the candidate phyla radiation (CPR or Patescibacteria). These bacteria have peculiar ribosomal structures, reduced metabolic capacities, small genome, and cell sizes, and a general host-associated lifestyle was proposed for the radiation. So far, most CPR genomes were obtained from groundwaters; however, their diversity, abundance, and role in surface freshwaters is largely unexplored. Here, we attempt to close these knowledge gaps by deep metagenomic sequencing of 119 samples of 17 different freshwater lakes located in Europe and Asia. Moreover, we applied Fluorescence in situ Hybridization followed by Catalyzed Reporter Deposition (CARD-FISH) for a first visualization of distinct CPR lineages in freshwater samples. RESULTS: A total of 174 dereplicated metagenome-assembled genomes (MAGs) of diverse CPR lineages were recovered from the investigated lakes, with a higher prevalence from hypolimnion samples (162 MAGs). They have reduced genomes (median size 1 Mbp) and were generally found in low abundances (0.02-14.36 coverage/Gb) and with estimated slow replication rates. The analysis of genomic traits and CARD-FISH results showed that the radiation is an eclectic group in terms of metabolic capabilities and potential lifestyles, ranging from what appear to be free-living lineages to host- or particle-associated groups. Although some complexes of the electron transport chain were present in the CPR MAGs, together with ion-pumping rhodopsins and heliorhodopsins, we believe that they most probably adopt a fermentative metabolism. Terminal oxidases might function in O2 scavenging, while heliorhodopsins could be involved in mitigation against oxidative stress. CONCLUSIONS: A high diversity of CPR MAGs was recovered, and distinct CPR lineages did not seem to be limited to lakes with specific trophic states. Their reduced metabolic capacities resemble the ones described for genomes in groundwater and animal-associated samples, apart from Gracilibacteria that possesses more complete metabolic pathways. Even though this radiation is mostly host-associated, we also observed organisms from different clades (ABY1, Paceibacteria, Saccharimonadia) that appear to be unattached to any other organisms or were associated with 'lake snow' particles (ABY1, Gracilibacteria), suggesting a broad range of potential life-strategies in this phylum. Video Abstract.
Keywords: metagenom; Metagenome; Animals; Cardiopulmonary Resuscitation; Phylogeny; hybridizace in situ fluorescenční; Lakes; zvířata; kardiopulmonální resuscitace; In Situ Hybridization, Fluorescence; fylogeneze; Metagenomics; Bacteria; jezera; metagenomika